Arbeitsmarkt 2030 - Wirtschaft und Arbeitsmarkt im digitalen Zeitalter - Vogler-Ludwig, Kurt; Düll, Nicola; Kriechel, Ben (W. Bertelsmann Verlag, 2021)
"The third long-term forecast by Economix estimates the implications of the recent influx of refugees on the German labour market as well as the qualification structure among the employees. At the same time, it forecasts the opportunities and risks of digitalisation.